Gambaran etnis dalam pengelolaan keuangan (studi empiris pada pedagang sembako di Kabupaten Sumba Timur) - Clara H. P. P. Medo Willi; Alliny Namilana Rambu Hutar (Jurnal Kajian Manajemen dan Wirausaha, 2022)
The presence of ethnic Bima and Wewewa in East Sumba, especially in the Matawai Market, Kota Waingapu District has provided many benefits through the contribution made in the trade sector. These two ethnic groups are able to control the market and can read opportunities and are able to meet consumer needs and become suppliers of basic necessities. By using a research sample of 40 people (20 ethnic Bima and the rest of Wewewa ethnicity) from 409 populations and the technical analysis of the data used in this research is a descriptive analysis showing that the Bima ethnicity obtained capital by making loans to banks as much as 45 percent, the Wewewa ethnic group obtained capital by making loans to the bank as much as 70 percent. In Bima, 80 percent of the total use of capital was to open a business, in the Wewewa ethnic group, the use of capital after obtaining capital was to use the capital to open a business and partly for personal needs as much as 55 percent. The Bima ethnic group invested as much as 70 percent, and for the Wewewa ethnic group, the investment made from the results of their business was as much as 50 percent.